Crystal structures of bis[4-(dimethylamino)pyridinium] tetrakis(thiocyanato-κN)manganate(II) and tris[4-(dimethylamino)pyridinium] pentakis(thiocyanato-κN)manganate(II) - Neumann, Tristan (Acta Crystallogr E Crystallogr Commun, 2018)
The crystal structures of the title salts, (C(7)H(11)N(2))(2)[Mn(NCS)(4)] (1) and (C(7)H(11)N(2))(3)[Mn(NCS)(5)] (2), consist of manganese(II) cations that are tetrahedrally (1) or trigonal–bipyramidally (2) coordinated to four or five terminal N-bonded thiocyanate ligands, respectively, into discrete anionic complexes. The negative charge is compensated by two (1) or three (2) 4-(dimethylamino)pyridinium cations, which are protonated at the pyridine N atom. The asymmetric unit of compound 1 consists of one anionic complex and two 4-(dimethylamino)pyridinium cations, whereas that of compound 2 consists of two anionic complexes and six 4-(dimethylamino)pyridinium cations, all of them located in general positions. These complexes are linked by N—H⋯S, C—H⋯S and C—H⋯N hydrogen-bonding interactions between the 4-(dimethylamino)pyridinium cations and the thiocyanate ligands into three-dimensional network structures.